2019
DOI: 10.1111/odi.13048
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative changes in knowledge and attitude toward oral health by oral health education

Abstract: Objectives: Perioperative oral health care can prevent postoperative complications, but it is also important to maintain oral health afterward to avoid later adverse events.This study examined (a) the relationship between knowledge and attitude toward oral health (KAOH) and oral/periodontal status (OPS) in patients receiving surgery, and (b) the changes in KAOH by perioperative oral health care and education. Methods:Patients receiving surgery who visited our hospital's dental clinic beforehand were prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Consistent with our findings, the improvement of attitude for the OH was also seen in other studies in similar settings including Bangladesh [57] and India [58]. Previous research indicated an increase or improvement in action planning for OH as key to achieving optimal behavior in the field of OH [59]. Experts believe that attitudes are obtained based on the individual experience of behavior or alternative experiences through learning from others; hence, as behavior is directly experienced, positive beliefs are strengthened in relation to the behavior outcome, and then act as incentives for its continuation [60].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, the improvement of attitude for the OH was also seen in other studies in similar settings including Bangladesh [57] and India [58]. Previous research indicated an increase or improvement in action planning for OH as key to achieving optimal behavior in the field of OH [59]. Experts believe that attitudes are obtained based on the individual experience of behavior or alternative experiences through learning from others; hence, as behavior is directly experienced, positive beliefs are strengthened in relation to the behavior outcome, and then act as incentives for its continuation [60].…”
Section: Discussionsupporting
confidence: 92%
“…These results affirm the importance of KAOF, similar to previous reports that patients with poor dental knowledge had poor periodontal health [ 17 , 18 ]. Patients with a poor understanding of oral health had poor oral hygiene and were found to improve their understanding of oral health and brushing frequency after education by dental hygienists [ 26 ]. According to the aforementioned studies, it is expected that ORF education will inculcate an understanding of ORF, resulting in improved ORF.…”
Section: Discussionmentioning
confidence: 99%
“…For better oral management, preoperative oral screening should be conducted as soon as possible. After the oral screening, patients could visit dentists to improve their oral status [22]. Moreover, if there is sufficient time until surgery, one can plan tooth extraction while considering the prevention of infective endocarditis and bloodstream disease [5,8,23].…”
Section: Discussionmentioning
confidence: 99%